Association between Helicobacter pylori infection and dental pulp reservoirs in Japanese adults - Komei Iwai; Isao Watanabe; Toshiro Yamamoto; Nagato Kuriyama; Daisuke Matsui; Ryota Nomura; Yuko Ogaya; Fumishige Oseko; Keiji Adachi; Shigeta Takizawa; Etsuko Ozaki; Teruhide Koyama; et al. (BMC, 2019)
Abstract Background Helicobacter pylori (H. pylori) colonize the stomach and are considered an etiological agent of gastric cancer. The oral cavity is a transmission route to the stomach, but the exact site of colonization has not yet been explicated. Our study investigated the association between H. pylori infection and presence in oral samples. Methods Dental pulp, supragingival plaque, and saliva from 192 patients visiting the Dentistry's outpatient clinic were collected for testing. The H. pylori ureA gene was identified via Nested PCR. Urine anti-H. pylori antibody test was utilized to detect infection. Results Twenty-five subjects were found to be antibody-positive. PCR analysis of dental pulp revealed that 23 subjects possessed the ureA gene. Twenty-one subjects were positive for both antibodies and genes in dental pulp. PCR testing revealed that 2 subjects were positive in dental plaque but negative for saliva. The subjects positive for H. pylori in dental pulp expressed clinical signs of severe dental caries. Conclusions H. pylori infected subjects expressed H. pylori in samples from the oral cavity. The main reservoir for infection within the oral cavity was determined to be dental pulp. Moreover, H. pylori are likely transmitted from dental caries to the root canal.